Avaliação do consumo de fármacos excretáveis pelo leite indicados para o gado bovino no âmbito das cooperativas da mesorregião metropolitana de Belo Horizonte em 1995 - Elza Conceicao de Oliveira Sebastiao (1997)
The 50 more consumed veterinarian drugs indicated for bovine cattle and that had at least, one milk excretable drug, in the ambit of cooperatives of mesorregiao metropolitana de Belo Horizonte, in 1995, were quantified by sold unities and classiied in anatomical-therapeutic-chemical (ATC) system, numbers of components active drugs, intrinsec therapeutic value, and risk nivels of adverse reaction production. The profile of drug use in the studied area was not racional. There was tendency in drug consumption of combined preparations (54%), drugs of not high therapeutic value (62%), considered inetiicacious, unnecessary and unfavorable benetitfrisk relation. The waste os financial recourses with questionable drugs was considerable, meaning R$918.357,63. The pharmacotherapeutic groups more consumed were the sistemic and gynecological antibiotics (66%) and ectoparasiticides (20%). There is an strong indicative that the detemtinat factors of this described consumption are the pharmaceutical Industry, as publicity, that induce the drug use without correspondating veterinarian orientation, salers drug indications, the deficient informations to the Rural Producers, and low veterinary assistance to the cooperatives associates about the drugs quality. In conclusion, for a rational drug use is sine qua mm condition the appropriate and conscious participation of all socity, component of drug-chain".